Promoting sleep and mental well-being in children: Protocol for a naturalistic pilot in-app study among users of the Aumio app. - Nadja Ruckser; Melissa Röcken; Jean Ochel; Alfred Wiater; Claudia Calvano (PLoS ONE)
Sleep problems are widespread among children and can have a negative impact on their development, everyday functioning and pose an additional burden on the parents. While there are numerous apps designed to improve children's sleep and help them fall asleep, little data are available regarding the feasibility, acceptability and efficacy. The purpose of this study is to conduct an initial analysis of the feasibility and acceptability of the Aumio app and an email psychoeducational module as well as preliminary efficacy on child's sleep quality and the associated factors well-being and parental stress. This research project is designed as a single-group pre-post design for a sample of 456 guardian-child dyads, with children aged 6-12 years. Participants will be recruited through the Aumio app as well as through advertisements in pediatric clinics and online. During the 12-week intervention, participants will be provided with the Aumio app and the parent-centred email psychoeducation module. At the beginning of the intervention and before the first app use (T0), six weeks after the first app use (T1), and immediately following the conclusion of the 12-week intervention (T2), the feasibility, acceptability and preliminary efficacy on children's sleep and health-related quality of life as well as parental stress will be examined. The study will examine the association between the intensity of the Aumio app use and the endpoints to improve feasibility and acceptability by synthesizing recommendations for use. This pilot study can provide important insights into an app targeting child's sleep problems in naturalistic, uncontrolled settings. Through this study, the existing research gap regarding app-based interventions for improving infant sleep will be addressed. Results will stimulate further development and research in the area of evidence-based mobile health interventions for children and their parents.